Analisis Sistem Pengendalian Internal Atas Pemberian Kredit Multiguna dalam Mengurangi Kredit Bermasalah pada PT. BPD Sultra Cabang Utama - Rachmawati Rachmawati; Sri Rachmawati Rachman (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to determine the application of the internal control system over the provision of multipurpose loans in reducing non-performing loans. The type of research used is a type of qualitative descriptive research. The data used is primary data, namely data collected through interviews. The results of this study show that the implementation of the internal control system at PT. BPD Sultra Main Branch is very adequate, namely by implementing 5 internal control components according to COSO consisting of: (1) Control environment, (2) Risk assessment, (3) Control activities, (4) Information and Communication, and (5) Monitoring activities